1972
DOI: 10.1002/eji.1830020609
|View full text |Cite
|
Sign up to set email alerts
|

“Spontaneous” B cell activation due to loss of normal mouse serum suppressor

Abstract: holmNormal mouse spleen cells initiate synthesis of immunoglobulins in vitro in the presence of fetal calf serum and in the absence of specific antigen following the removal of regulatory suppressor(s) present in normal syngeneic mouse serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(55 citation statements)
references
References 15 publications
2
52
1
Order By: Relevance
“…We stress that in normal spleen cultures :~ Identical cultures contained either 3 )< 106 SRBC or 3 X 106 HRBC, All cultures were assayed on day 4 using the erythrocytes indicated in the plaque-forming assay and each figure represents the mean of duplicate cultures. (23)(24)(25) and in adult mice (26) (d) A background immune response to TNP is also found. When nude spleen cells are cultured with different concentrations of LPS and assayed at various times using HRB C or TNP-HRBC as the indicator in the plaque-forming assay, PFC specific for both HRBC and TNP can be distinguished.…”
Section: Effect Of Antigen On Lps-induced Immunementioning
confidence: 89%
“…We stress that in normal spleen cultures :~ Identical cultures contained either 3 )< 106 SRBC or 3 X 106 HRBC, All cultures were assayed on day 4 using the erythrocytes indicated in the plaque-forming assay and each figure represents the mean of duplicate cultures. (23)(24)(25) and in adult mice (26) (d) A background immune response to TNP is also found. When nude spleen cells are cultured with different concentrations of LPS and assayed at various times using HRB C or TNP-HRBC as the indicator in the plaque-forming assay, PFC specific for both HRBC and TNP can be distinguished.…”
Section: Effect Of Antigen On Lps-induced Immunementioning
confidence: 89%
“…The final erythrocyte cell pellet obtained by centrifugation at 200 g for 10 min was added to an appropriate volume of EBSS. Following the modified procedure of Bullock and Moller (1972), splenocytes (50 μl), 400 μl agar solution (250 mg agar/50 ml EBSS, pH 7.2), SRBC (25 μl) and diluted (1:3) guinea pig complement (25 μl) were mixed together, poured into a bacteriological culture dish and overlayed with cover glass (45×50 mm). The agar plates were allowed to solidify and were incubated at 37 o C in 5% CO 2 incubator for 3 h. PFCs were counted using a dissecting microscope.…”
Section: Plague-forming Cell (Pfc) Assaymentioning
confidence: 99%
“…SRBC, stored in Alsever's solution and washed three times in balanced salt solution (BSS) before use, were coupled to NNP (4-hydroxy-3,5-dinitro-phenacetyl) as described by Pasanen and Miikelä [15], Assays for detection of antihapten PFC were performed with a modification of the local hemolysis in gel assay as described by Bull ock and Möller [5], Cells were harvested with a plastic spatula and washed twice in cold BSS and adjusted to the desired concentration. 0.6 ml of 0.5% agar (Difco Laboratories, Detroit, Mich.) in BSS containing 0.5% DEAE dextran (Pharmacia, Uppsala, Sweden) was added to 3 ml tubes which were kept at 46 °C in a water bath.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that concanavalin A, phytohemagglutinin and lipo polysaccharide (LPS)-induced increase in DNA synthesis is diminished, when lympho cytes are cultured with NMS [13]. It has also been reported that the polyclonal acti vation of plaque-forming cells (PFC) by fe tal calf serum is inhibited by syngeneic mouse serum [5]. However, in a recent pa per the authors report that when studying the influence of autologous NMS on LPS activation, only the LPS-induced DNA syn thetic response is affected, whereas LPS-in duced polyclonal PFC formation is intact [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation